Effectiveness of the Ecological Program “Saltando por su salud” in the Promotion of Physical Activity and Self-Efficacy in Third-Grade School Children - Álvarez Bogantes, Carlos (2016)
The purpose of this paper was to evaluate the effectiveness of the “Saltando por su Salud” program on the variables of physical activity and self-efficacy in third grade School children, using an ecological model. Study Design: A quasi-experimental design was used for 4 months. Subject: 34 boys and 32 girls took part with an average age of 9.2 years. 30% of the participants were overweight or obese. Intervention: the intervention included: structuring of PE to encourage moderate physical activity, physical education activities for life and behavioral skills, along with the development of environmental conditions and social support to promote physical activity during recess. Results: Children in the intervention group had a significant increase in physical activity (p <.001) measured by pedometers. In addition, they showed an improvement in the self-efficacy to overcome barriers for physical activity (p <.001). Conclusions: The “Saltando por su Salud” program improved time spent on physical activity and strategies to overcome barriers for physical activity This study demonstrated that using existing school resources and an ecological approach, It is possible to build healthier school environments.